Faith and Security: The Role of Religion in Curbing Youth-involved Kidnapping in the Post-amnesty Niger Delta, Nigeria (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The Niger Delta region has long been a flashpoint of instability, shaped by youth restiveness, militancy and proliferation of non-state armed actors. Although the post-amnesty period brought a relative reduction in open conflict, it witnessed a troubling rise in youth-involved criminal activities, notably kidnapping for ransom. This paper examines the evolving role of religious institutions, particularly Pentecostal movements, in addressing the socio-economic and moral conditions that fuel youth involvement in kidnapping in the post-amnesty Niger Delta. The paper explores the significance of religious movements in countering kidnapping, which has remained a major security concern to the people of the region. This qualitative study sourced data from observation, media reports and Niger Delta conflict tracker. The framework of analysis was the principles of conflict transformation. Religious organizations are increasingly pivotal in redirecting youth from criminality through moral reorientation, community integration and vocational support. Religion, when purposefully aligned with human development initiatives, serves as a grassroots mechanism for discouraging kidnapping and promoting sustainable peace in the region.